The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s11605-014-2662-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antibiotic Prophylaxis in Necrotizing Pancreatitis: A Meta-Analysis

Abstract: Antibiotic prophylaxis does not significantly reduce the incidence of infected pancreatic necrosis but may affect all-cause mortality in acute necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 37 publications
0
31
0
6
Order By: Relevance
“…Overall, 6 of the 18 studies concluded that prophylactic antibiotics significantly reduced total mortality, which includes 17 RCTs, 18,[20][21][22][23][24] while 4 studies concluded that prophylactic antibiotics significantly reduced the incidence of pancreatic necrosis. 18,20,25,26 The two most recent studies included, 20,21 supported the use of antibiotics. Ukai et al 20 included six RCTs in which antibiotics (within 72 hours) were administered early in patients with acute necrotising pancreatitis, with the exclusion of studies with delayed or indeterminate timing of antibiotic administration.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 6 of the 18 studies concluded that prophylactic antibiotics significantly reduced total mortality, which includes 17 RCTs, 18,[20][21][22][23][24] while 4 studies concluded that prophylactic antibiotics significantly reduced the incidence of pancreatic necrosis. 18,20,25,26 The two most recent studies included, 20,21 supported the use of antibiotics. Ukai et al 20 included six RCTs in which antibiotics (within 72 hours) were administered early in patients with acute necrotising pancreatitis, with the exclusion of studies with delayed or indeterminate timing of antibiotic administration.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
“…The study advocates further RCTs to determine the effect of the timing of antibiotic administration on mortality and pancreatic necrosis infection. Lim et al 21 analysed nine RCTs and two cohort studies to determine the benefits of prophylactic antibiotics. The study did not show a significant reduction in the incidence of pancreatic necrosis in the total study population, RCT population or cohort population.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
“…Antibiotic prophylaxis to reduce infective complications in acute pancreatitis was evaluated in a series of randomized trials [4][5][6][7][8][9][10][11][12]. However meta-analyses of these trials do not support antibiotic prophylaxis in acute pancreatitis [13][14][15]. Summarising this evidence, the International Association of Pancreatology/American Pancreatic Association (IAP/APA) produced evidence-based guidelines in 2013 for the management of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Encontramos 18 revisiones sistemáticas [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18] que incluyen 19 estudios controlados aleatorizados reportados en 20 artículos, [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38] y dos estudios observacionales [39], [40]. Esta tabla y el resumen en general se basan en los estudios aleatorizados.…”
Section: Acerca Del Conjunto De Evidencia Para Esta Preguntaunclassified
“….5867/medwave.2014.07.6004) debido a la reciente disponibilidad de dos nuevas revisiones sistemáticas, posteriores a la publicación del artículo original [1], [2].…”
unclassified